Ocular and adnexal rhinosporidiosis : the clinical profile and treatment outcomes in a tertiary eye care centre - Mithal, C; Agarwal, P; Mithal, N (Nepalese Journal of Ophthalmology, 2012)
Introduction: Rhinosporidiosis may mimic a burst chalazion or a simple conjunctival polyp. Objective: To study the demography, histopathological evaluation, treatment modalities, their outcomes and recurrence rates in patients clinically and histopathologically diagnosed as ocular and adnexal rhinosporidiosis. Patients and methods: The study was conducted in the Department of Orbit, Oculoplasty and Oncology at a tertiary eye care centre in South India. Fifty patients were included who were diagnosed with ocular and adnexal rhinosporidiosis. The conjunctival and lid mass underwent complete excision. All patients with rhinosporidiosis of the lacrimal system underwent dacryocystectomy (DCT) with care taken to avoid spilling the spores. Diagnosis was confirmed histopathologically. Results: The mean age at presentation was 30.42 years, standard deviation( SD) being 16.89 (1 - 70 years). The mean follow-up was 14.2 months (12 months - 18 months) . The most common site was conjunctiva (n = 26 eyes, 52 %), followed by the lacrimal sac ( n = 13, 26 %) and lids (n = 11, 22 %). All the cases were treated by surgical excision with cautery at the base. There was a single recurrence (2 %) involving the lacrimal sac. Endonasal polypectomy combined with exploration in the sac region was done. There were no further recurrences during subsequent follow-up. Conclusion: Rhinosporidiosis is an ocular disorder with high recurrence rates reported. We recommend histopathological examination in every case following excision biopsy for conclusive diagnosis. Recurrence rates can be very low if a complete meticulous excision coupled with cauterization of the lesion is performed. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5849 NEPJOPH 2012; 4(1): 45-48